TREND KASUS BARU INFEKSI HUMAN IMMUNODEFICIENCY VIRUS (HIV) DI INDONESIA PERIODE TAHUN 2012–2016 - Adriansyah, Agus Aan; Firdausi, Nurul Jannatul (UNUSA Press, 2017)
Abstract: Countries in Southeast Asia have a very high HIV (